A Science of Diplomacy - T. V. Zonova (Vestnik MGIMO-Universiteta)
MGIMO is a unique educational and research center in the field of diplomacy both as science and art. Russian scholars and diplomats can be called pioneers in understanding the contemporary diplomacy. The creation in 1973 of the Department of the diplomatic service and development of a new scientific field of diplomatic studies has brought tangible results already in 1970-1980. Real breakthrough in this area was the creation of the Problem Research Laboratory at MGIMO. Its members conducted research in the theory and practice of negotiation process. MGlMO produced the first Russian textbook "Theory and Methodology of analysis of international negotiations" by A.V. Zagorski and M.M. Lebedeva, and Y. Dubinin. In this area MGIMO manifests itself as an undisputed leader. It is remarkable that at this time some American authors noted that Russian developments in the negotiations studies were more advanced than in the US. Information revolution, abandonment of a mind frame of bipolar world - all this has created very favorable conditions for reaching a qualitatively higher level of analysis of diplomatic institutions, structures and methods. A possibility of converting the study of diplomacy in the field of modern political science became evident. Having preserved the tradition of the historical and international law studies, MGIMO scientists started analyzing complex diplomacy as a political institution, evolving according to its own rules and in accordance with certain laws. One of the first significant studies of diplomacy as a political institution was the work by Tatiana Zonova "A Modern Model of Diplomacy. Origins Evolution and Prospects". Comprehensive training and research activities at MGIMO provides the basis for the successful training of young diplomats and researchers so that they can work effectively and meet the challenges of international relations and world politics of the 21 century.